A Bibliometric Study of 3D Printing's Educational Applications - Arifin, Samsul (JURNAL VOKASI TEKNOLOGI INDUSTRI (JVTI), 2024)
Using 3D printing in education research will continue to grow over the next few years, according to experts. It may be seen in a broad variety of scientific fields as well. An examination of 1,384 3D printing research articles published in 793 scientific journals and authored by 5,438 authors was conducted in this study (103 single-authored documents and 5,335 multi-authored documents). The goal of this study is to identify the trending topic in 3D printing right now. R software's Bibliometrix tool was used to extract data from Scopus and run it via VOSviewer, which was then loaded into the database. We've chosen the world's most significant publications, journals, authors, nations, and affiliations based on citation analysis criteria. While keywords and phrases are likely to be the most important issues and conclusions of the research, it is probable that some major patterns and concerns contained in the complete text are not properly reflected in our study. The development of patterns in 3D Printing should be examined in future studies to give scientific knowledge, as well.